Experimental analysis on circular concrete-filled steel tubular beam-columns under unequal load eccentricities. (15th May 2022) - Albero, V.; Ibañez, C.; Hernández-Figueirido, D.; Piquer, A.
Highlights: Tests on unequal eccentrically loaded slender concrete-filled steel tubular beam-columns. Influence of eccentricity ratio and column slenderness are studied. Deflection, and longitudinal strain are analyzed. Moment – curvature behaviour is provided for further model validation. Provisions on second order moment from Eurocode 4 and AISC 360–16 are assessed. Abstract: This paper presents eight experimental tests on circular concrete-filled steel tubular (CFST) beam-columns loaded under unequal eccentricities at both ends. This loading scheme has not been widely studied yet in previous research works on CFST columns, but it may be very common into industrial or residential multi-storey frames, where both ends are subjected to different bending moments. Tests results revealed that the ultimate resisting load increases when the column is loaded under unequal eccentricities compared to what is loaded under equal eccentricities. However, under certain conditions, the column ductility decreases. Also, the equations provided by the Eurocode 4 and AISC 360–16 for second order effects were assessed. Specifically, the equivalent moment factors, βor Cm, were calculated from experimental data and compared to those given by the standards. Although Eurocode 4 presents more accurate predictions, both codes provide safe predictions for higher slenderness beam-columns but unsafe predictions for double curvature members with low slenderness. In view of the results, further research is needed to improve the equivalent moment factor proposals including additional parameters apart from the loading eccentricity ratio.